Stress and health risk behaviors among university students - Ellaine Santana de Oliveira; Antonia Fabiana Rodrigues da Silva; Kadija Cristina Barbosa da Silva; Tatiana Victória Carneiro Moura; Açucena Leal de Araújo; Ana Roberta Vilarouca da Silva
ABSTRACT Objective: To analyze the level of stress and its relationship with health risk behaviors among university students. Method: Cross-sectional analytical study carried out at a higher education institution in Picos-PI. A total of 377 students were evaluated for socio-demographic and academic variables, stress profile, sleep quality, alcohol use, smoking habits and level of physical activity. The Statistical Package for the Social Sciences (SPSS), version 20.0 was used for data processing and analysis. Results: Sleep quality was poor for 65.3% of the subjects, and sleep disturbances were found in 17.0%. Stress was observed in 68.7% of the sample. Stress was associated with the following variables: gender, time in the institution, poor sleep quality. Conclusion: Most of the students evaluated present some level of stress associated with poor sleep quality, which is a risk to the quality of life of these individuals.